In situ study on radiation response of a nanotwinned steel. (November 2022) - Shang, Zhongxia; Niu, Tongjun; Sun, Tianyi; Xue, Sichuang; Fan, Cuncai; Chen, Wei-Ying; Li, Meimei; Wang, Haiyan; Zhang, Xinghang
Abstract: Recent radiation studies on nanotwinned pure metals suggest that twin boundaries are appealing defect sinks, as they can transport and eliminate radiation-generated defects. However, radiation response of twin boundaries in nanotwinned steels is less well understood. Here, we investigate the microstructural evolution of a nanotwinned steel using in situ Kr ++ irradiation to 4 dpa at ambient temperature. The in situ results show that nanoscale deformation twins in steels can effectively suppress the formation of ordered dislocation loop rafts. Furthermore, the formation of dislocation loop rafts and Frank loops depends prominently on twin spacing. The underlying mechanisms of the enhanced radiation resistance are discussed. The present study makes a positive step forward for the potential application of nanotwinned structural steels to nuclear reactors. Graphic abstract: Image, graphical abstract